Manajemen Produksi Kerupuk pada Perusahaan Dagang (PD) Kerupuk Toha Kota Serang - Aspriana Aspriana; Lani Salsabilla; Nurul Hanifah; Rasel Amarta (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
PD Toha crackers have been established since 1979. There are 2 types of crackers, namely white crackers (rose) and yellow crackers (opak). Curly rose crackers and opak crackers are generally side dishes and snacks made from tapioca flour and spices that are mixed with warm water then molded and steamed until cooked, followed by the drying and roasting process, then frying, labeling and packaging. These curly rose crackers have a savory taste, are shiny white and have a crispy texture. This Trading Company (PD) aims to find out how to maintain the quality of crackers and increase their selling value. The method of implementing this program is carried out through the stages of market survey, pre-production, production, marketing and business analysis. The production process of curly rose crackers is carried out for 10 production times and produces 400 packages. Each production produces 40 packages of curly rose crackers with 37 cracker contents which are sold at a price of Rp. 5,000 / package. The curly rose cracker product has a B/C ratio of 1.30 with a profit rate of 32%, so this product can be said to be feasible to run. The ingredients needed in making curly rose crackers are tapioca flour, tuna, garlic, salt, pepper, and water. The production process of curly rose crackers has several stages, namely preparation of raw materials, weighing, mixing, molding, steaming, drying, roasting, frying and packaging. The critical point in making curly rose crackers is at the molding and frying stages.